Czech Republic: Czech National Bank’s Role in the Monetary Policy - Tomášková, Eva; Radvan, Michal (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter deals with monetary policy in the Czech Republic, in which the Czech National Bank plays a crucial role. Broadly, the objective of monetary policy is to ensure price stability. Notably, Czech Republic has not joined the Eurozone – it is a member of the European System of Financial Supervision and cooperates with the European Systemic Risk Board and European Supervisory Authorities. While, prior to the COVID-19 pandemic, the Czech Republic met most of the Maastricht criteria for the euro, with the exception of compliance with normal exchange rate fluctuation margins, the situation has changed with the pandemic: currently, it only meets the criterion of the total general government debt-to-GDP ratio. Meanwhile, the most important factor for decision-making is the degree of alignment of the Czech economy with the Eurozone, which is key to outweighing the gains from the introduction of the euro over the losses from its own monetary policy. Presently, it is not possible to state that the Czech economy is significantly aligned with the euro area. As a non-member of the euro area, the Czech Republic is not obliged to join the European Banking Union. Important to note is that the Czech Republic regularly prepares a study that analyses all relevant aspects of its possible participation in the European Banking Union to help it make an informed decision on whether to join the European Banking Union before adopting the euro. These studies show that the banking sector in the Czech Republic is highly stable; therefore, it is increasingly advantageous for the Czech Republic to remain outside the European Banking Union. Notably, the Czech Republic used interest rates and foreign exchange interventions to ensure the stability of the economy during the pandemic and, subsequently, the Russo-Ukrainian war.Keywords: Czech monetary policy, Czech National Bank, euro, banking, monetary policy, COVID-19 pandemic, Russo-Ukrainian war